Changing behavior of friction coefficient for high strength bolts during repeated tightening. (November 2020) - Liu, Zhifeng; Zheng, Mingpo; Yan, Xing; Zhao, Yongsheng; Cheng, Qiang; Yang, Congbin
Abstract: Due to its strength advantage, high strength bolts are able to provide larger clamping force. However, the changing behavior of friction coefficient during repeated tightening will adversely affect the tightening torque - clamping force relationship. To ensure reliable clamping force of high strength bolts, an easy implement experimental method to investigate the changing behavior of friction coefficient is put forward in this work. The constraint torque of bolt head, as well as the tightening torque and clamping force, was measured during tightening. Friction coefficient interval of bolt underhead is obtained according to the preset assumptions and experimental results. Based on the mechanical equilibrium relationship of the bolt during tightening, thread reaction torque can be obtained to calculate the friction coefficient of threads and bearing surface. Three cases are considered, namely without lubricant, lubrication at threads and nut surface. Statistical analysis was carried out through replicated experiments to investigate the effect of clamping force on the changing behavior of friction coefficient. Without lubrication, repeated tightening caused the increasing of friction coefficient, which resulted in a reduction of clamping force. When using a lubricant, it can protect the contact surface, and the obtained clamping force during repeated tightening was more stable. Experimental results showed that the proposed method can be used to investigate the changing behavior of friction coefficient during repeated tightening. Highlights: An easy implement experimental method to investigate the changing behavior of friction coefficient is put forward in this work. Based on the mechanical equilibrium relationship of the bolt during tightening, thread reaction torque can be obtained to calculate the friction coefficient of threads and bearing surface. Statistical analysis was carried out through replicated experiments to investigate the effect of clamping force on the changing behavior of friction coefficient. The friction and wear of the threaded fasteners during repeated tightening was observed and analyzed.